Pengaruh Lingkungan Internal Restoran terhadap Niat Beli Ulang - Harsoyo, Titik Desi (STIE Widya Manggala, 2008)
This research aims to empirically test the effect of menu, employees service and ambience on repurchase intention of family restaurant and fast food restaurant. A self-report questionnaire is used to measure quality of menu, employees service, ambience, satisfaction and repurchase intention. Data are collected from 432 respondent, consist of 182 respondents for family restaurant and 250 respondent for fast-food restaurant. The result of the two types of restaurant indicates a difference inly on employees service. The effect of employees service on repurchase intention of family restaurant is direct, meanwhile of fast food is mediated by satisfaction. Menu and ambience affect repurchase intention on the both types of restaurant.